Translational Activation of Oskar mRNA: Reevaluation of the Role and Importance of a 5' Regulatory Element. - Kanke, M.; Macdonald, P.M. (PLoS ONE, 2015)
Local translation of oskar (osk) mRNA at the posterior pole of the Drosophila oocyte is essential for axial patterning of the embryo, and is achieved by a program of translational repression, mRNA localization, and translational activation. Multiple forms of repression are used to prevent Oskar protein from accumulating at sites other than the oocyte posterior. Activation is mediated by several types of cis-acting elements, which presumably control different forms of activation. We characterize a 5' element, positioned in the coding region for the Long Osk isoform and in the extended 5' UTR for translation of the Short Osk isoform. This element was previously thought to be essential for osk mRNA translation, with a role in posterior-specific release from repression. From our work, which includes assays which separate the effects of mutations on RNA regulatory elements and protein coding capacity, we find that the element is not essential, and conclude that there is no evidence supporting a role for the element only at the posterior of the oocyte. The 5' element has a redundant role, and is only required when Long Osk is not translated from the same mRNA. Mutations in the element do disrupt the anchoring function of Long Osk protein through their effects on the amino acid sequence, a confounding influence on interpretation of previous experiments.